2016
DOI: 10.1016/j.bbmt.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, Alcohol Use Disorder, and Age Predict Outcomes after Autologous Hematopoietic Cell Transplantation for Lymphoma

Abstract: Autologous hematopoietic cell transplantation (HCT) is a treatment option for many patients diagnosed with lymphoma. The effects of patient-specific factors on outcomes after autologous HCT are not well characterized. Here, we studied a sequential cohort of 754 patients with lymphoma treated with autologous HCT between 2000 and 2010. In multivariate analysis, patient-specific factors that were statistically significantly associated with non-relapse mortality (NRM) included hematopoietic cell transplantation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…2 Comorbidities and age were reported to impact the prognosis of patients with lymphoma undergoing auto-HSCT. 3,4 However, the assessment of organ dysfunction prior to auto-HSCT has not been well studied in an effort to predict complications and outcome after auto-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…2 Comorbidities and age were reported to impact the prognosis of patients with lymphoma undergoing auto-HSCT. 3,4 However, the assessment of organ dysfunction prior to auto-HSCT has not been well studied in an effort to predict complications and outcome after auto-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Wildes et al found that a higher CCI score was negatively associated with survival after ASCT among 159 patients with NHL 23. Graf et al showed that higher hematopoietic cell transplantation-specific comorbidity index scores predicted non-relapse mortality after ASCT among 754 lymphoma patients (HR 1.94, 95% CI: 1.0–3.7) 24. Primary refractory disease has also been shown to be associated with impaired survival after ASCT; in the CORAL study, 3-year OS was 39% and 64% for patients with refractory and relapsed disease, respectively 8.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol intake, hypertriglyceridemia, and DKA are well-established risk factors for the development of AP and may explain their higher incidence. Alcohol use disorder has been found to be an independent risk factor for mortality in HSCT patients [ 18 ]. Despite adjusting for alcohol use disorder, our study revealed higher mortality in the AP group.…”
Section: Discussionmentioning
confidence: 99%